Is Unity between Reason and Domain Indissoluble? Critique of Reason according to Horkheimer and Habermas - Contreras, Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The aim of this article is to consider whether the equation between reason and domain belongs to the essence of reason, and consequently, its own critical self-reflection would be selfcontradictory, or if on the contrary, being this a historical situation, its regulatory fundamentals are possible. To clarify this, we are going to confront the works of Horkheimer Critique of Instrumental Reason, Dialectic of Enlightenment and Reason and Self-preservation to the rethinking of the question made by Habermas in his work Knowledge and Human Interests.